2000
DOI: 10.1097/00003072-200006000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of a Malignant Hurthle Cell Carcinoma by Tc-99m Sestamibi Cardiac Imaging

Abstract: A 60-year-old man reported chest pain and shortness of breath. His medical history was negative for myocardial infarction but positive for "mini strokes" and type 2 diabetes mellitus. Tc-99m sestamibi cardiac imaging revealed an abnormal focus of increased activity in the left lobe of the thyroid. Although no cardiac abnormalities were found, a I-123 thyroid scan subsequently showed a solitary hypofunctioning nodule involving the middle and inferior aspects of the left lobe of the thyroid, which fine-needle as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[6,7] MIBI has fortuitously been observed to show uptake in benign and malignant tumors including the lung, thyroid, brain, lymph node metastasis, bone and in breast cancer. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The routine evaluation of myocardial perfusion scans includes the reconstructed SPECT images localized just to the myocardium. The routine protocol for the evaluation of myocardial perfusion scans includes the inspection of the planar, cine raw data and the reconstructed SPECT images limited just to the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] MIBI has fortuitously been observed to show uptake in benign and malignant tumors including the lung, thyroid, brain, lymph node metastasis, bone and in breast cancer. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The routine evaluation of myocardial perfusion scans includes the reconstructed SPECT images localized just to the myocardium. The routine protocol for the evaluation of myocardial perfusion scans includes the inspection of the planar, cine raw data and the reconstructed SPECT images limited just to the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports describe various tumors visualized as incidental NCF during cardiac perfusion studies. Among these are focal liver photopenia representing colon cancer metastasis [2], diffuse appendicular skeleton uptake representing multiple myeloma [3,4], focal thyroid uptake representing Hurthle cell carcinoma [5], anterior mediastinal activity representing malignant thymoma [6], and focal lung uptakes representing bronchogenic carcinoma [7,8], ectopic parathyroid adenoma [9], and carcinoid [10]. In addition, there is a growing collection of reports describing non-neoplastic NCF, such as pleural effusions [11,12], pericardial effusions [13,14], large ovarian cyst [15], large liver cyst [16], large renal cysts [17], large hiatal hernia [17,18], cholecystitis [19,20], lactation [21], gastric wall uptake [22], benign lung nodules [23], acute pulmonary embolism [24], ascites [25,26], gastric reflux [27], and nonspecific dyspepsia [22].…”
Section: Introductionmentioning
confidence: 99%
“…Unexpected detection of malignancies during imaging studies using 99m Tc sestamibi, either parathyroid scintigraphy or myocardial perfusion study, has been reported many times before. However, most of the lesions in prior publications were soft tissue tumors, including those in the thyroid, 6,7 lungs, 8,9 breast, 10–12 mediastinum, 12–14 kidney, 15 and liver 16 . Multiple myeloma can also have elevated sestamibi activity 17,18 .…”
mentioning
confidence: 99%